Magnetic (CoFe2O4)0.1(CeO2)0.9 nanocomposite as effective pinning centers in FeSe0.1Te0.9 thin films. (11th December 2015) - Huang, Jijie; Chen, Li; Jian, Jie; Tyler, Kevin; Li, Leigang; Wang, Han; Wang, Haiyan
Abstract: Magnetic epitaxial (CoFe2 O4 )0.1 (CeO2 )0.9 nanocomposite layers were incorporated into superconducting FeSe0.1 Te0.9 thin films as either a cap layer or a buffer layer. Both capped and buffered samples show an enhancement of the superconducting property compared to the reference sample without the incorporated layer, while the capped one shows the best pinning properties of all the samples. Specifically for the capped sample, the critical temperature is 12.5 K, while the self-field critical current density increases to as high as 1.20 MA cm −2 at 4 K. Its value shows a slower decrease with increasing applied magnetic field, with the lowest power-law exponent α values (derived following by the plot) of 0.20, 0.23 and 0.33 at 2 K, 4 K and 8 K, respectively. This nanocomposite capped sample also exhibits a high upper critical field of 166 T, which indicates its potential in high field applications. This pinning method provides an effective way of enhancing the superconducting property of iron chalcogenide thin film.